Najpierw , (dla tych co by sie zgubili , np.4/9 oznacza ułamek cztery-dziewiąte ;) ,
Oblicz :
(-3,6)×4/9=
(-2,1)×(-4 2/7)=
-7/8÷(-5,6)=
9/10÷(-3/4)=
(-1 1/2)÷(-0,06)=
(-2 2/3)÷1,2=
2/3÷(-6)=
(-0,45)÷1 4/5=
(-2,75)÷(-2,2)=
(-3,5)÷(-1 2/5=

Gdyby coś było nie jasne to pisać ! :)

1

Odpowiedzi

Najlepsza Odpowiedź!
2010-02-23T16:23:05+01:00
(-3,6)×4/9=-1,6
(-2,1)×(-4 2/7)=2,4
-7/8÷(-5,6)=4,9
9/10÷(-3/4)=-1,2
(-1 1/2)÷(-0,06)=25
(-2 2/3)÷1,2=-2,2222222222222222
2/3÷(-6)=-0,111111111111111111
(-0,45)÷1 4/5=-0,81
(-2,75)÷(-2,2)=1,25
(-3,5)÷(-1 2/5=2,5